Proper Relay Reduction And Route Breakage Prediction In Blueooth Scatternet Scheduling (International Journal of Engineering and Computer Science, 2014)
Bluetooth is a promising new technology for short range wireless connectivity between mobile devices. By constructing a piconet, Bluetooth device establishes link and communicates with other devices in a master–slave manner. The piconets are combined to form the Scatternet and communicate through the Relay /bridge node. So the performance of the Scatternet highly depends on the relays and its degree and mobility. The unnecessary relay causes scheduling overhead and inefficient use of limited resources.   Thus, optimum number of relays should be maintained without any control overhead. The proposed method achieves this goal through relay reduction with load balancing and route breakage prediction. Therefore by implementing the proposed protocol the Scatternet performance will get improved due to reduced packet loss and route recovery time.